Assessing drought tolerance of cotton (Gossypium spp.) RIL populations using agrophysiological and stress indices - Mukhammadaliev, Ravshanbek I; Buriev, Zabardast T; Rakhmanov, Bakhtiyor K; Alibekova, Ra’no Kh; Bozorov, Ilkhomjon E; Muhammadov, Yo'ldoshbek A; Mamajanov, Akramjon B; Mamanazarov, Sharofiddin I; Khusenov, Naim N; Norbekov, Jurabek K; et al. (Plant Science Today, 2026)
In this study, 80 samples (F6) of recombinant inbred line (RIL) populations derived from the wild cotton species Gossypium tomentosum and Gossypium mustelinum were comprehensively evaluated under control and drought conditions. The main objective of the study was to identify lines that were tolerant, sensitive and stable to drought stress conditions. The stress tolerance of the lines was assessed using physiological and yield-based stress indices. The main evaluated physiological parameters were relative leaf water content (RWC), excised leaf water loss (ELWL) and yield (Yp, Ys). Stress indices, including STI, GMP, MP, SSI, YI, YSI and TOL, were also calculated. Based on the obtained data, the level of stress tolerance of RIL samples was determined using principal component analysis (PCA). According to the results of the analysis, RIL-36 (STI = 1.44, YSI = 1.44, SSI = –2.07, TOL = –12.15), RIL-45 (Ys = 58.17, YI = 1.62, GMP = 59.90) and RIL-27 (Ys = 56.93, STI = 1.20, YSI = 1.20) were found to be resistant lines. RIL-25 (YSI = 1.24, SSI = –1.12), RIL-63 (SSI = –0.47), RIL-76 (YSI = 1.10) and RIL-24 (YSI = 1.05) lines also showed positive results. In contrast, RIL-19 (Ys = 19.66, STI = 0.39, SSI = 2.90), RIL-07 (YSI = 0.47, TOL = 33.94), RIL-06, RIL-39 and RIL-72 were evaluated as sensitive lines with low Ys and high SSI. In conclusion, the integration of agrophysiological parameters with the stress tolerance index has been shown to be effective in differentiating drought-tolerant, tolerant, sensitive and stable RIL genotypes. The inclusion of wild Gossypium species in the breeding stock will expand the genetic base of cultivated cotton and increase the possibility of creating water-stress-tolerant varieties.